Psycho-pedagogical Research of Inclusive Education in the Undergraduates Training - Alyohina S. V. (Moscow State University of Psychology and Education, 2015)
The author examines the cultural and historical psychology as a methodological basis of research in the inclusive process of education. The article presents the current trends in research of inclusive education such as the design of organizational and psychological and pedagogical conditions for reinforcing the cultural norms of inclusion in the school: individual development in inclusive education; designing an inclusive educational environment. The article describes the logic of the research master students training. The author suggests for discussion some variants of design and research tasks in order to form the necessary research and development competencies of master students. The author is convinced that the quality of an inclusive process in basic education linked to the development of inclusive practice based on scientific research. Cultural-historical framework and its main idea becomes the methodological basis of psychological research as it claims a leading role of social environment in the development and educating of children